Assessing the Risk of Brain Tumors in Young Populations: A Review - Jaiswal, Nicky Kumar; Singh, Kumari Priyanka; Kumar, Dinesh (Indian Journal of Pharmacy Practice)
Brain tumors represent a significant health burden globally, with their incidence steadily rising. India, as a populous country, bears a considerable share of this burden. Epidemiologically, brain tumors present a complex scenario in India, with variations in incidence rates across different regions and demographic groups. Factors such as age, gender, socioeconomic status and geographic location influence the prevalence and distribution of brain tumors within the Indian population prospects in the field of brain tumor research and treatment in India are promising, with ongoing efforts focused on personalized medicine, targeted therapies, immunomodulation and precision oncology In conclusion, brain tumors represent a significant healthcare challenge in India, necessitating a comprehensive understanding of their epidemiology, etiology, diagnosis and treatment. Addressing the multifaceted challenges associated with brain tumor management requires collaborative efforts and innovative approaches to improve patient outcomes and quality of life.
Keywords: Brain tumors; Epidemiology socioeconomic; Socioeconomic; Geographic location